2008
DOI: 10.1055/s-2007-965331
|View full text |Cite
|
Sign up to set email alerts
|

Heat Acclimation and HSP-72 Expression in Exercising Humans

Abstract: The purpose of this research was to determine the effect of a 7-day heat acclimation protocol on HSP-72 expression in human skeletal muscle, and to examine the relationships between molecular and physiological markers of heat acclimation. Ten recreationally active male subjects (age = 23.3 +/- 2.81 yrs, VO(2peak) = 3.85 +/- 0.11 L . min (-1)) completed a 7-day heat acclimation protocol consisting of cycling at 75 % of VO(2peak) in a hot environment (39.5 degrees C, 27 % RH). Muscle biopsies were obtained on da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 30 publications
5
28
1
Order By: Relevance
“…Among the five or so studies that have examined intracellular HSP70 during acclimation, two show evidence to the contrary in intracellular studies of HSP70 during acclimation (Marshall et al 2007;Watkins et al 2008). Our results apparently contribute to the evidence that basal intracellular HSP70 does not reflect whole-body acclimation.…”
Section: Hsp70 and Apoptosis During Acclimationmentioning
confidence: 49%
See 2 more Smart Citations
“…Among the five or so studies that have examined intracellular HSP70 during acclimation, two show evidence to the contrary in intracellular studies of HSP70 during acclimation (Marshall et al 2007;Watkins et al 2008). Our results apparently contribute to the evidence that basal intracellular HSP70 does not reflect whole-body acclimation.…”
Section: Hsp70 and Apoptosis During Acclimationmentioning
confidence: 49%
“…Relatedly, lower core temperatures and heart rate maximums were seen in the acclimation study of Marshall et al (2007), which found no change in intracellular HSP70 during early acclimation. Although Watkins et al (2008) also saw no change in intracellular HSP70 with observations of heart rates that reached between 165 and 185 bpm, their observed maximum core temperature was approximately 38.8°C and they measured HSP70 of muscle tissue lysates. If we attribute to possible differences in cell type or tissue response of HSP70, as has been shown (reviewed in Yamada et al 2008), it is possible that in order to perceive HSP70 responses in circulating cells, acclimating subjects must experience extreme hyperthermia and cardiovascular strain during daily exercise-heat exposures.…”
Section: Hsp70 and Apoptosis During Acclimationmentioning
confidence: 84%
See 1 more Smart Citation
“…143,167,168 Elevation of HSP70 in response to high-intensity and long-term training is also found after an 11-d training program, but not in response to short or moderate intensity exercise. 146,[169][170][171][172] Besides exercise intensity, training status and the type of exercise seem to exert considerable effect on HSP70 expression. In untrained subjects, 5-8 wk of triceps brachii training produce a significant increase in HSP70, 173 whereas 12 wk of concentric contraction of biceps brachii decrease HSP70 protein expression in trained athletes.…”
Section: Exercise and Hsp70 Protein Expression In Animalsmentioning
confidence: 99%
“…Although heat acclimation is recommended to athletes, to persons in certain occupations, and to military personnel at risk of heat illness, it is surprising that only recently have investigators begun to investigate the cellular adaptations (Yamada et al 2007;McClung et al 2008;Watkins et al 2008;Magalhães et al 2010). The present study was the first to test the hypothesis that changes in protein expression with whole-body acclimation in humans HA could modify the cellular response to stressors normally experienced by heat stroke patients.…”
Section: Discussionmentioning
confidence: 99%